(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper aims to scrutinize the portrayal of subaltern entities in Indian regional literature with special reference to the short story ‘The Shroud’ by Munsi Premchand. This research focuses to contemplate this particular piece of writing from Marxist project and will unmask the socio-political and socio-economic conditions where unprivileged group of society are trapped to exploitations and opperessions. The present article also investigates the identity crisis and the formation of false consciousness of downtrodden by the exploitative forces especially during the early twentieth century in India.